Effect of Self-Controlled Practice on Neuro-Cortical Dynamics During the Processing of Visual Performance Feedback. Issue 5 (3rd September 2021) - Jaquess, Kyle J.; Lu, Yingzhi; Ginsberg, Andrew; Kahl, Steven; Lu, Calvin; Ritland, Bradley; Gentili, Rodolphe J.; Hatfield, Bradley D.
Abstract: Evidence has accumulated that learners participating in self-controlled practice can both acquire skills and process task-relevant information more effectively than those participating in externally controlled practice. However, the impact of self-controlled practice on neuro-cognitive information processing during visual performance-related feedback has received limited investigation. We expected that individuals participating in self-controlled practice would exhibit elevated neuro-cognitive information processing, as assessed via electroencephalography (EEG), compared with those engaged with externally controlled practice. Participants practiced a golf-putting task under self-controlled or externally controlled (yoked) conditions while EEG data were recorded. Results indicated that EEG theta power was maintained at an elevated level during the feedback period in the self-controlled group relative to the yoked group. The yoked group did not display increases in theta power until the time at which the ball stopped. Both groups displayed similar improvement over the course of the experiment. Correlational analyses revealed that performance improvement within each group was related differently to EEG theta power. Specifically, the self-controlled group displayed positive relationships between theta power and performance improvement, while the yoked group displayed negative relationships. These results have implications regarding the relative effectiveness of self-controlled and externally controlled practice and the instances in which they may provide the most benefit.